Exploring the Psychological Dimensions of Mobile-Assisted Language Learning (MALL) in English Language Education - Vega, Nofvia De; Basri, Muhammad; Nur, Sahril (Utan Kayu Publishing, 2023)
This research investigates the psychological aspects influencing student engagement with Mobile-Assisted Language Learning (MALL) in English language education. The study contributes to a deeper understanding of the role that students' attitudes, personalities, expectations, and motivations play in shaping their learning experiences. The research employs a narrative inquiry approach coupled with semi-structured focus group interviews. A purposive sampling method based on individual factors such as gender, age, and culture was used to select participants from Universitas Borneo Tarakan. The qualitative analysis identified key themes and patterns from the students' narratives about their MALL experiences. The findings reveal that positive attitudes towards MALL, genuine interest in language learning, and high expectations significantly enhance student motivation and active participation in MALL activities. Furthermore, robust institutional support emerged as crucial for the successful implementation of MALL programs. These insights suggest that by understanding these psychological dimensions and ensuring adequate institutional support, educators can improve students' experiences with MALL. It has implications for fostering enhanced engagement and success in language learning.